AB1220-HPR Attentional Bias Towards Subjectively Unconscious Threat-Related Information in Fibromyalgia. (9th June 2015) - Mercado, F.; Barjola, P.; Peláez, I.; Cardoso, S.; Guerra, V.; Gόmez-Esquer, F.
Abstract : Background: Fibromyalgia constitutes a chronic pain syndrome that has been also characterized by an altered cortical processing of emotional stimulation (Montoya et al., 2005). Furthermore, several studies have indicated that such dysfunction in the emotional processing could be related to the presence of attentional biases towards threat-related information (Duscheck et al., 2014). However, little is known about neural correlates of the time course of attentional biases in fibromyalgia and their clinical significance. Objectives: To explore neural correlates of the time course of early attentional biases in fibromyalgia. Methods: To test this issue, 40 participants (twenty fibromyalgia patients- FM- and twenty healthy volunteers –HV-) were asked to perform concurrent but distinct target distractor paradigm . Stimulation consisted of the presentation of a set of visual elements, some of them remaining outside the subject's awareness (eg., spiders –threatening stimuli- or snowflakes –neutral stimuli-) and others being consciously perceived (numbers from 1 to 9). These numbers were presented at the centre of the screen and the out-of-awareness elements were situated peripherally forming frames all around in each number. Each image lasted 50 ms. Participants had to press a key when the central number was under 5, and a different key, when it was over 5. Event-related potentials (ERP) were recorded at sixty scalp electrodes. Temporal and spatial principal component analyses were employed to define and quantify ERP components. Results: ANOVAs indicated that posterior regions of the P1 component (temporal factor 4) were sensitive to the interaction between type of stimulus by group (p<0.05). Specifically, FM patients as compared to HV showed higher amplitudes to threatening information than the neutral one even when it was subjectively non-consciously perceived. Conclusions: Present results show enhanced activation at cortical visual processing regions to threat-related information in fibromyalgia patients even when it was unconsciously processed. This early/automatic attentional bias to emotionally negative stimulation in these patients could play a relevant role as a strong mechanism to maintain and worsening their pain-related symptoms. Therapeutical strategies aimed to train controlled attentional skills may be helpful (Vago et al., 2011). References: Duscheck, S., Werner, N.S., Limbert, N., Winkelmann, A. & Montoya. P. (2014). Attentional bias toward negative information in patients with fibromyalgia syndrome. Pain Medicine, 15, 603-612. Montoya, P., Pauli, P., Batra, A. & Wiedemanm, G. (2005). Altered processing of pain-related information in patients with fybromialgia. European Journal of Pain, 9, 293-303. Vago, R.D., & Nakamura, Y. (2011). Selective attentional bias towards pain-related threat in fibromyalgia: preliminary evidence for effects of mindfulness meditation training. Cognitive Therapy and Research, 35, 581-594. Acknowledgements: Supported by grant PI13/01759 from the Ministry of Economy and Competitiveness: Institute of Health Carlos III (ISCIII) of Spain. Disclosure of Interest: None declared